On-farm technologies in social context: Improving local adaptive capacities and inclusive scaling mechanisms in Nandi County, Kenya - Gichuki, Leah (International Livestock Research Institute, 2022)
A presentation on how to improve local adaptive capacities and inclusive scaling mechanisms for climate-smart agriculture in Kenya. It was delivered at the inception workshop for the CGIAR Initiative for Livestock and Climate by Birgit Habermann and Leah Gichuki in Nandi and Bomet counties in Kenya.